ANALISIS KANDUNGAN BAHAN ORGANIK DAN BAKTERI Patogen (E. coli) DI PELABUHAN BASTIONG DAN PANTAI KAYU MERAH KOTA TERNATE - Mesrawaty Sabar; Inayah Inayah (TECHNO: JURNAL PENELITIAN, 2016)
Recently, the development of coastal zone becomes the center of attention and tends to increase their use. This situation is due to the limited availability of urban land, so investment led to the coastal area. The effect of land activities causes a negative impact on the environment, for example, is pollution. Organic waste is the main source of pollution that entering to beach and piling on coastal waters. The types of organic domestic waste are from household activities such as washing, rinse, carcasses of animals and plants, pesticide waste, pond, and hatchery activities. The study aims to analyze the content of organic matters and pathogens bacteria (E.coli) and to know the relationship of both above parameters. The study is conducted approximately one month at Bastiong Port and Kayumerah Beach on Ternate city, North Maluku Province. The observation parameters of BOD, COD, TSS, dissolved organic matter, and Bacteria E.coli are carried out on Productivity and Water Quality Laboratory of Hasanuddin University. The measurement of other parameters (pH, temperature, and salinity) is conducted by in situ. The result shows that the highest concentration of organic matter obtained at station 1 point 2, as same as bacteria found on the largest number on that station. On station 2 points 2 is obtained the lowest number of organic matter and also bacteria. The high content of organic matter on station 1 is due to the electricity industry that produces waste effluents i.e. oil. This waste cause increases organic matters in waters. Keywords: E.coli, dissolved organic matter, a bacterial pathogen